Of Her Own Volition: Barbara Godard as a Case Study of the Translator's Agency - Voyer, Anne (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2016)
Critic, translator, and editor Barbara Godard has been a central figure in the landscape of Canadian literature over the past four decades as one of the leaders in theories of feminist translation. Her devotion to feminism, and her presence on the literary and theoretical scenes in Canada and abroad, helped bring translation to the forefront of theoretical discourse, and contributed to what Kathy Mezei described as “the recognition of translation as a vital literary activity and theoretical site.” Refusing to practice self-effacement in her translation work, Godard flaunted her signature, leaving creative “tracks” for the attentive reader to follow in the text. In doing so, she deliberately and complicitly worked with the source, actively participating in the creation of meaning. An examination of her “position traductive” offers helpful insight into her politics of feminist translation. This essay explores Godard’s translation criticism and practice, and etches out her ideological and critical articulations of her process.